The Past Informing the Future: An Interview with Earl Santee, Populous - Rachel Hickey (Journal of Applied Sports Management, 2023)
The facility expert in focus is Earl Santee, a senior principal, global chair, and founder at Populous. Populous is the leading architectural and design firm in the sport facility sector. Santee, having been has been recognized for numerous awards, including the Sports Business Journal’s 2019 Class of the Champions: Pioneers & Innovators in Sports Business, is excellently positioned to offer an expert perspective on the past, present, and future of sport facility design
Keywords: Architecture; Facility Design; Operation Management; Sport Facilities; Venues